In situ long-term monitoring of recolonization by fungi and lichens after innovative and traditional conservative treatments of archaeological stones in Fiesole (Italy). (August 2018) - Pinna, Daniela; Galeotti, Monica; Perito, Brunella; Daly, Giulia; Salvadori, Barbara
Abstract: The research complements a study (Pinna et al., 2012) carried out to evaluate the effectiveness of mixtures of consolidants and water-repellent products (tetraethylorthosilicate, methylethoxy polysiloxane, Paraloid B72), with biocides (tributyltin oxide, dibutyltin dilaurate, copper nanoparticles) applied in situ to prevent biological growth on stones. The mixtures were tested over time on trial areas of three substrates - marble, sandstone, and plaster – in the archaeological site of Fiesole (Firenze, Italy). The 8-year-long study showed that the recolonization of the three substrates after the conservation treatment related mainly to their bioreceptivity and to the climatic conditions. Although the mixtures of water repellents and consolidants with biocides and copper nanoparticles were effective in reducing the recolonization, they did not play a crucial role in preventing biofilms and lichens growth. This study demonstrated that it was not possible to draw common conclusions regarding the products' performance on the examined stones. Copper nanoparticles proved to be a suitable alternative to traditional biocides because they did not alter stones colour and contributed to the prevention of recolonization. The study provided information on the succession of fungi and lichens on untreated and treated stones, as well as on the variations of water repellency of treated stones. Highlights: Mixtures of consolidants and water-repellents with biocides and copper nanoparticles. In situ application on marble, sandstone, and plaster. Recolonization of fungi and lichens on untreated and treated stones. The stones showed very different bioreceptivities. Copper nanoparticles proved to be a suitable alternative to traditional biocides.